2018
DOI: 10.1111/1756-185x.13460
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Health Assessment Questionnaire Disability Index and physical performance in rheumatoid arthritis and osteoarthritis

Abstract: ObjectivesTo investigate whether the Health Assessment Questionnaire Disability Index (HAQ‐DI) reflects objective measures of physical function in people with osteoarthritis (OA) and rheumatoid arthritis (RA).MethodsIn total, 139 people, 71 with RA fulfilling the American College of Rheumatology (ACR) criteria (1987) and 68 with OA fulfilling ACR criteria for OA of the hip or knee, completed the HAQ‐DI. Physical function was assessed using Timed Up and Go (TUG), 30 seconds Sit to Stand (STS), grip strength dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
1
14
0
1
Order By: Relevance
“…A major impact of reduced grip force on disability has been demonstrated in several previous studies (1,3,18,19,32), including a survey of the cohort investigated in the present study (6). This suggests that hand training should be bene cial in early RA.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A major impact of reduced grip force on disability has been demonstrated in several previous studies (1,3,18,19,32), including a survey of the cohort investigated in the present study (6). This suggests that hand training should be bene cial in early RA.…”
Section: Discussionsupporting
confidence: 71%
“…DAS28), have been found to be moderately correlated (17). A moderate association has also been found between HAQ-DI and grip force in patients with RA (18). Therefore, it is important to study the course of disability as a separate outcome in RA (11).…”
Section: Introductionmentioning
confidence: 99%
“…This is illustrated by our results, showing that participants with RA had significantly lower grip strength when compared to participants with OA, despite having similar levels of ALM, which could have been caused by localised pain in the hands. Also, a recently published paper on the same cohort showed that hand function is more important than pain in affecting grip [49]. Although this could be viewed as a possible limitation of this study, there is still little agreement on sarcopenia cut-scores and even less is known about the most appropriate sarcopenia definitions in disease specific populations.…”
Section: Discussionmentioning
confidence: 86%
“…Az osteoarthrosisban szenvedők funkcionális állapotának jellemzésére Health Assessment Questionnaire (HAQ-) [21,22] tesztet, a fájdalom felmérésére vizuális analóg skálát (VAS) alkalmaztunk. Az életminőséget mindkét csoportban EuroQol-5D (EQ-5D-3L) [23] kérdőívvel vizsgáltuk.…”
Section: Funkcionális éS éLetminőségtesztekunclassified